Roberto Marchesini. Etologia del desiderio. Riscoprive la propria animalitÃ - Macelloni , Manuela (Journal of Ecohumanism, 2024)
This interview addressed to Professor Roberto Marchesini concerns one of his main spheres of reflection: the concept of desire. Contrary to the classical humanist tradition, in fact, Marchesini develops a conception of desire as internal redundancy, a vital force, that is in constellation with the concept of Spinoza’s conatus. In this meeting we explored what he expressed in his book Ethology of Desire. Rediscover your own animality.